Is functional movement screening indicative of lumbopelvic and trunk kinematics during a prolonged non-exhaustive running bout? - Boratino, Alessandra Vairo Peres (2022)
Functional screening tests are performed in sports settings aiming to recognize neuromuscular deficits and asymmetries, guiding preventative strategies often expecting to improve the running mechanic. So far, no studies have validated those tests in a prolonged run. The findings may provide clinicians with insights into the utility of conventional physical assessment. The study aimed to investigate the association of 3D trunk and lumbopelvic kinematics during a non-fatiguing running and four functional screening tests. Methods: Ten recreational runners were included (age 27,91±5 y). The protocol was 3 repetitions of each functional test (squat, single leg squat, lunge, and hurdle step) followed by a 40-minute over-ground running at a self-selected pace. Hip, pelvic and trunk kinematics were assessed with a 3-D motion analysis Results: Similar trunk, lumbopelvic, and hip kinematics pattern during the knee peak flexion during the midstance; few subjects have had interlimb kinematics asymmetries during running (pelvic list, pelvic rotation, and lateral bending- p<.001). Running and functional tests demonstrated major differences (p<.001) in lateral bending and pelvic list, pelvic tilt, and axial and pelvic rotation. In addition, there were positive, moderate to strong correlations only for pelvic list and rotation among running and functional tests. Discussion/conclusion: There were no signs of fatigue, and similar kinematics were observed in running and tests. The interlimb asymmetries could be caused by a lack of neuromuscular control or anatomical differences. The correlation between the lumbopelvic and trunk was inconsistent, so these tests should not be used as the only source of the neuromuscular motor.